New data on the stomatocyst of Spiniferomonas abrupta Y. Nielsen (Chrysophyceae, Chromulinales) - Bessudova, Anna; Firsova, Alena D.; Likhoshway, Yelena V. (Phytotaxa, 2025)
Of the more than 800 stomatocyst morphotypes described in studies worldwide, about 36 morphotypes have been assigned to species of silica-scaled chrysophytes. Using scanning electron microscopy, we observed the formation of stomatocysts of the rare boreal species Spiniferomonas abrupta. Based on the presence of species-specific siliceous plate-scales on the surface, Stomatocyst 513 Firsova & Bessudova, its affiliation to S. abrupta was determined. The stomatocyst is primarily spherical or widely obovate, with an obconical collar and a regular pore surrounded by a flat planar annulus. This morphotype was found at the mouth of the Ida River, a right tributary of the Angara River, in Eastern Siberia, in May at a water temperature of 11.3 °C and pH 8.4.